Using spectrum set-asides to address distributional objectives: lessons from Canada, New Zealand, South Africa and the United States - Bronwyn Howell; Petrus H. Potgieter (International Telecommunications Society (ITS), 2024)
This paper critically examines the effectiveness of spectrum set-asides as a policy tool to address distributional objectives in telecommunications across four diverse national contexts: Canada, New Zealand, South Africa, and the United States. Spectrum allocation is a crucial factor for the provision of telecommunications services and by extension, for citizens' participation in the digital economy. While economic theory supports auction-based allocations to maximize market efficiency, set-asides aim to facilitate access for disadvantaged groups or to stimulate competition. This study employs case studies from the selected countries to evaluate the impact of these set-asides on market efficiency, competition, and economic development. In Canada, set-asides intended to encourage new market entrants have led to higher spectrum costs and inefficiencies due to speculative behaviour. In New Zealand, allocations to the indigenous Maori population have raised concerns over long-term sector efficiency and capital accessibility. South Africa's policy mandates spectrum allocations to entities with significant ownership by historically disadvantaged persons, with mixed outcomes on market dynamics and social equity. Meanwhile, the United States' approach includes grants rather than direct spectrum set-asides, offering a potentially less distortive model. The findings suggest that while set-asides can support social objectives, they often introduce inefficiencies and fail to achieve the desired economic outcomes. The paper concludes by discussing the implications for future spectrum policy, advocating for careful consideration of the trade-offs between equity and efficiency in spectrum management.
Keywords: 330; Spectrum Allocation; Telecommunications Policy; Digital Economy; Market Efficiency; Competitive Supply; Economic Development; Regulatory Strategies